TALABALARNING INNOVATSION FAOLIYATINI RIVOJLANTIRISHDA MUZEY MANBALARINING AHAMIYATI - Xalmuratov, I.T. (SCIENCE and SOCIETY, 2025)
In this article, are highlighted the use of reproductions, slides and photographs of well-known works from the museum collection in the course of lessons and extracurricular activities gives very good results, the importance of viewing exhibition halls, museum exposition halls in the development of innovative activities of future architects and the stages of development.